Attitudes and knowledge of students on sexuality in three secondary schools - Filipović, Tomislav, medicinski tehničar (Array, 2020)
Introduction. Sexuality of children and adolescents in Croatia is still considered a taboo, and sexually transmitted diseases are a significant global public health problem that is constantly growing. As a frequent consequence of irresponsible sexual behaviour and early sexual intercourse, we are faced with the problem of juvenile, most often unwanted, pregnancy. Contraceptives are used to prevent sexually transmitted diseases and unwanted pregnancies, and the most vulnerable group are the adolescents. The primary task is to educate the youth prior to them entering active sexual life. Aim. To collect and analyse data on sexual habits, attitudes and knowledge of adolescents. To assess the need for additional education and preventive programmes. Methods. 130 high school students, aged 17-19, participated in the survey. For testing purposes, a questionnaire was used. The questionnaire was conducted voluntarily and was completely anonymous, and a written consent was obtained from parents of juvenile participants. Results. The adolescent subjects in this study showed insufficient knowledge of sexuality, namely the menstrual cycle, contraceptives and emergency contraception, and sexually transmitted diseases. They showed knowledge of things they could get acquainted with on a daily basis through the media and other information outlets. Conclusion. According to the results obtained by the research, we can conclude that higher quality education of the youth is necessary, with the aim of expanding their knowledge of sexuality in order to prevent sexually transmitted diseases and the occurrence of unwanted juvenile pregnancies.